2016
DOI: 10.17140/rpaoj-1-103
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Advantages of Peripheral Nerve Blockade Translate to Decreased Length of Stay and Improved Patient Satisfaction

Abstract: Citation Kerfeld MJ, Hambsch ZJ, McEntire DM, et al. Physiologic advantages of peripheral nerve blockade translate to decreased length of stay and improved patient satisfaction. ABSTRACTPeripheral nerve blockade is an effective modality involved in controlling perioperative pain. When compared with patient controlled analgesia, neuraxial analgesia, and other anesthetic methods such as periarticular infiltration, peripheral nerve blocks yield superior pain control and reduce length of hospitalization. Not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(48 reference statements)
0
4
0
1
Order By: Relevance
“…A similar study by reported a success rate of 76.7% using US-guided ONB and 90% of patients using USguided nerve stimulation. 12 Another study by reported similar results; in their study, the success rate of ONB was 88% using US-guided nerve stimulation and 70% in US-guided nerve block only. 13 Finally, another study reported a success rate of 100% in the US-guided nerve stimulation group and only 80.6% in the US-guided nerve block-only group.…”
Section: Discussionmentioning
confidence: 67%
“…A similar study by reported a success rate of 76.7% using US-guided ONB and 90% of patients using USguided nerve stimulation. 12 Another study by reported similar results; in their study, the success rate of ONB was 88% using US-guided nerve stimulation and 70% in US-guided nerve block only. 13 Finally, another study reported a success rate of 100% in the US-guided nerve stimulation group and only 80.6% in the US-guided nerve block-only group.…”
Section: Discussionmentioning
confidence: 67%
“…11 Among these, peripheral nerve blocks are cost effective anaesthesia techniques which are used to achieve proper anesthesia by avoiding airway instrumentation and hemodynamic consequences of general and spinal anesthesia. 9,11,17 As we have mentioned earlier that several findings suggested ONB as to effective facilitating complete resection of a urinary bladder tumour by immobilizing the surgical field, avoiding nerve stimulation and jerks as well as preventing other complications like bleeding or bladder perforation, while doing TURBT. [8][9][10] Hence, for decades, ONB has become essential for performing TURBT safely and effectively.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,17 As we have mentioned earlier that several findings suggested ONB as to effective facilitating complete resection of a urinary bladder tumour by immobilizing the surgical field, avoiding nerve stimulation and jerks as well as preventing other complications like bleeding or bladder perforation, while doing TURBT. [8][9][10] Hence, for decades, ONB has become essential for performing TURBT safely and effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teknik ini merupakan alternatif penggunaan opioid dosis tinggi dalam menurunkan angka kejadian hipertensi, takikardia, serta stres neuroendokrin. [6][7] Sekresi hormon adrenokortikotropik (ACTH) akibat stimulasi respons stres operasi bermanifestasi terhadap peningkatan sekresi katekolamin dan kortisol oleh glandula adrenal. Stimulasi kedua hormon tersebut mengganggu kerja insulin dan meningkatkan glikogenolisis sehingga terjadi peningkatan kadar glukosa darah.…”
Section: Pendahuluanunclassified